Assessment of agility and multi-directional movement with the T agility test in young handball players - Woszczek, Iwona; Szczypiór-Piasecka, Karina; Antczak, Krzysztof; Mińko, Alicja (Journal of Education, Health and Sport, 2021)
INTRODUCTION: T Agility Test is one of the tests that evaluates multidirectional movement in connection with the speed of movements. The T test also evaluates dynamic stability, also known as agility. It has been defined as the ability to maintain a controlled body position and quickly change the direction of movement without losing balance. The test is useful in sports such as handball or basketball. In handball, players get a lot of injuries, the most common of which occur during training and matches when there is a clash with other players. The most common injuries concern the wrist, ankle, shoulder and knee joints. OBJECTIVES OF THE WORK: 1. Comparison of dynamic stability in youth training handball. 2. Impact of injury on handball T test result. 3. Usefulness of the T test for assessing dynamic stability and multidirectional movement in athletes. MATERIAL AND METHODS: 23 young handball players were tested with the T Agility test and the questionnaire was conducted. To carry out the test, accessories such as cones, stopwatch and centimeter were needed. The cones were arranged in the shape of the letter T. The player's task was to overcome the designated distance as quickly as possibile. RESULTS: The average test time T was 10.95 s. The fastest player reached 9.15 s and the worst time was 12.11 s. Most players (14) suffered ankle injuries. Sprains of the joint, p = 0.56 and rupture / tear of the muscle / tendon, (p = 0.48) were frequent injuries. The most common injuries in the wrist joint concerned fractures of the fingers, p = 0.29 and finger knockout p = 0.14. CONCLUSIONS: 1. This T test is useful for assessing dynamic stability and multidirectional movement of athletes. 2. Suffered injuries do not have a significant impact on the T test result. 3. T test is a useful tool in the training process.